PENANAMAN NILAI DISIPLIN PADA ANAK-ANAK PANTI ASUHAN AL-MAA'UUN PURWOKERTO - Ilham Karuniawan, Iing; Hidayat, Fahri (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
Non-formal education is one of the educational pathways in Indonesia and has the same role in educating the nation's children, one of which is learning carried out in orphanages. Education in an orphanage is not just about transferring knowledge, but is broader in terms of instilling educational character values, especially disciplinary values. The aim of this research is to explore the instilling of disciplinary values in children at the Al-Ma'uun Orphanage in Purwokerto. This research uses a qualitative approach. Data was collected through interviews, observation and documentation. Data analysis is simultaneously carried out in three ways, namely data reduction, presentation, and inference or data verification. Triangulation was carried out to ensure the accuracy of the data obtained. The results of this research are the instilling of Disciplinary Values in the Children of the Purwokerto Al-Maa'uun Orphanage carried out through five activities, namely: 1) Motivation Increasing Activities (activities showing motivational videos, sowing traditions, and Koran recitation activities, 2) Education and training (Congregational Prayer Discipline, Monday and Thursday Fasting Discipline, Discipline in participating in Islamic boarding school activities, Discipline in going in and out of the orphanage, Discipline in returning home agreements, Discipline in carrying out roan (cleaning), 3) Leadership (leaders set a good example), 4) Enforcement of Rules (written rules and unwritten rules), and 5) Rewards and punishments (congregational prayer penalties, student activity penalties, and penalties for permission to leave home). From this it can be seen that instilling disciplinary values in children at the Al-Maa'uun Orphanage in Purwokerto can run well and in a programmed manner.